Stepwise growth of crystalline MoS2 in atomic layer deposition - Cho, Ah-Jin; Ryu, Seung Ho; Yim, Jae Gyun; Baek, In-Hwan; Pyeon, Jung Joon; Won, Sung Ok; Baek, Seung-Hyub; Kang, Chong-Yun; Kim, Seong Keun (Royal Society of Chemistry, 2022)
Atomic layer deposition (ALD) is considered a promising growth technique for transition metal dichalcogenides (TMDCs) because it ensures uniformity and homogeneity of the TMDC grains. However, the poor crystallinity of ALD-grown TMDCs remains a critical challenge. Although crystallinity depends on the growth mechanism, the growth behavior of crystalline TMDCs in ALD is unclear. We investigated the growth behavior of highly crystallized molybdenum disulfide (MoS2) by ALD at 650 degrees C with an extra pulse of remote H-2 plasma. Growth at high temperatures using the activated species aided surface diffusion of the adsorbates. The ALD process facilitates repeated growth and saturation of MoS2, unlike the normal ALD of 3D bulk materials, where the film thickness monotonically increases with the number of ALD cycles. This unique behavior resulted from the evolution of the basal plane without dangling bonds. On the basal plane, MoS2 lateral growth dominates vertical growth, and prolonged incubation is required for nucleation on the basal plane. The grain size is small (up to two monolayers) because of the limited mobility on SiO2, and the grains of the third layer grow to a few hundred nanometers. These findings provide insights into the development of ALD technology for application to high-quality TMDCs.